Post COVID-19 Pandemic Employment Challenges and Indonesia's Opportunities to Take Advantage of the Demographic Bonus - Muhyiddin Muhyiddin (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2023)
Human resource development has become a priority for the Government of Indonesia 2019-2024 period with the aim of producing a competent, resilient, productive, and competitive workforce. The Ministry of Manpower has set Nine Big Leaps (9 Lompatan) to achieve this goal, which consists of: 1) BLK transformation; 2) Employment Link and Match; 3) Transformation of Job Opportunities Expansion Program; 4) Development of Young Talents; 5) Foreign Job Markets Expansion; 6) New Vision of Industrial Relations; 7) Labor Inspection Reform; 8) Development of Employment Digital Ecosystem; and 9) Bureaucratic Reform. The COVID-19 pandemic that stormed the world at the end of 2019 and entered Indonesia in the second quarter of 2020 had changed everything. Conditions and structure of the economy were shaken violently, as well as the employment sector, both in Indonesia and globally, experienced quite difficult and challenging times. The open unemployment rate had been increasing in Indonesia, especially for experienced workers, indicating that there had been terminations of employment (Pemutusan Hubungan Kerja) due to the pandemic. Even though Indonesia's pandemic conditions have been slowly improving, the impact on the employment sector remains significant. The pandemic condition improvement has opened up opportunities for the Indonesian economy to bounce back, which still remains to be wary of the possibility of a K-shaped recovery, in which the middle to lower economic group will get an economic downturn whilst the middle to the upper economic group will prosper. To prevent this, Indonesia needs to ensure that the recovery that occurs is an inclusive economic recovery that improves the quality, competitiveness, and productivity of its workforce. Education level and job mismatch are still challenges that must be faced. In addition, Indonesia must maximize its demographic benefits by increasing the quality and productivity of its workforce to encourage inclusive economic growth while monitoring potential future demographic and employment threats. This 2023 Employment Outlook was prepared with its primary objective of reviewing employment developments and dynamics in Indonesia from 2019 to 2022; analyzing the issues and challenges faced in employment in 2023, especially in dealing with the COVID-19 pandemic which is starting to recede; and formulating Indonesia's employment development strategy for its future.